2008
DOI: 10.1007/bf03178589
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of Fuji IP Cassette Type PII and application for radiation oncology quality assurance tests and portal imaging

Abstract: The advancement of digital imaging has prompted more medical institutions to go filmless. The computed radiography (CR) system is becoming an important tool not only in diagnostic imaging, but also in radiation oncology. A new CR system that was specially designed for the use in radiation oncology, Fuji IP cassette type PII has been introduced to the market in the middle of year 2006. This project aimed to study some basic physical characteristics of this new type of cassette and explore its application for pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Other researchers such as Peace et al [8] and Soh et al [9] have demonstrated the successful use of CR for LINAC QA. Peace et al [8] designed a test tool for light field radiation congruence by embedding a 1 mm diameter lead wires in a Perspex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other researchers such as Peace et al [8] and Soh et al [9] have demonstrated the successful use of CR for LINAC QA. Peace et al [8] designed a test tool for light field radiation congruence by embedding a 1 mm diameter lead wires in a Perspex.…”
Section: Discussionmentioning
confidence: 99%
“…We used a double exposure technique and found a good contrast with the tungsten markers. To check the coincidence between light field and radiation field, Soh et al [9] placed four coins at each of the four edges of a square light field size (15 cm × 15 cm). They found the CR could be used even though their approach was very simplistic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPID is known as a useful QA tool for visual verification of light and radiation fields because of its high resolution, and many related studies have been reported [4,6,11,12]. In addition, various methods have been implemented to improve and supplement the disadvantages of the conventional QA method [10,13]- [16]. In QA using EPID, which replaces the film, the inconvenience caused by using the film can be improved, and the radiation field can be quantitatively analyzed.…”
Section: Jinst 17 P11038mentioning
confidence: 99%